BIBLIOMETRIC ANALYSIS OF INNOVATION IN THE SOCIAL ECONOMY. ITS THEORETICAL IMPLICATIONS - Victor Dante AYAVIRI-NINA; Sofia Alejandra MATOS AROCA; Gabith Miriam QUISPE FERNANDEZ; Edgar Anibal RODRIGUEZ; David FLORES RUIZ; Gerardo Mauricio ZURITA VACA (Geo Journal of Tourism and Geosites)
The present research develops a bibliometric analysis of innovation in the social economy, the study provides a comprehensive vision of the current state of the field and highlights the most relevant publications, authors, sources and research topics, taking as its general objective to analyze the behavior and advances in the literature about innovation in the social economy through a bibliometric analysis, in this way Scopus and Web of Science (WoS) were considered as data sources, forming a database of 304 registered articles, of which 111 belong to Scopus and 193 Web of Science (WoS). In the processing and representation of data, the Bibliometrix and VoSviewer programs were used, which highlights information on trends, citation analysis, H index, analysis of co-occurrences, keywords, affiliations on innovation research in the social economy. The growing scientific production underlines the growing importance of the social economy as a driver of sustainable economic development. Geographic distribution, thematic trends, and identification of influential contributors contribute to future research and practical efforts within this field.